Emerging Systemic Therapies for Colorectal Cancer - Veenstra, Christine M.; Krauss, John C. (Clinics in Colon and Rectal Surgery, 2018)
Despite advances over the past 20 years in colorectal cancer (CRC) screening, diagnosis, and treatment, survival outcomes remain suboptimal. Five-year survival for patients with locally advanced CRC is 69%; 5-year survival drops to 12% for patients with metastatic disease. Novel, effective systemic therapies are needed to improve long-term outcomes. In this review, we describe currently available systemic therapies for the treatment of locally advanced and metastatic CRC and discuss emerging therapies, including encouraging advances in identifying novel targeted agents and exciting responses to immunotherapeutic agents.
Keywords: colorectal cancer; emerging therapies; targeted therapy; immunotherapy; clinical trials